Short-Term Salicylic Acid Treatment Affects Polyamine Metabolism Causing ROS–NO Imbalance in Tomato Roots - Ágnes Szepesi; Péter Poór; László Bakacsy (Plants, 2022)
The phytohormone salicylic acid (SA) can influence the polyamine metabolism in plants. Additionally, polyamines (PAs) can regulate the synthesis of SA, providing an exciting interplay between them not only in plant growth and development but also in biotic or abiotic stress conditions. The effect of SA on polyamine metabolism of leaves is well-studied but the root responses are rarely investigated. In this study, tomato roots were used to investigate the effect of short-term exposition of SA in two different concentrations, a sublethal 0.1 mM and a lethal 1 mM. To explore the involvement of SA in regulating PAs in roots, the degradation of PAs was also determined. As both SA and PAs can induce reactive oxygen species (ROS) and nitric oxide (NO) production, the balance of ROS and NO was analyzed in root tips. The results showed that 0.1 mM SA induced the production of higher PAs, spermidine (Spd), and spermine (Spm), while 1 mM SA decreased the PA contents by activating degrading enzymes. Studying the ROS and NO levels in root tips, the ROS production was induced earlier than NO, consistent with all the investigated zones of roots. This study provides evidence for concentration-dependent rapid effects of SA treatments on polyamine metabolism causing an imbalance of ROS–NO in root tips.